EVALUASI KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PENAMBANGAN BATUBARA PT. DASRAT SARANA ARANG SEJATI PARAMBAHAN, DESA BATU TANJUNG, KEC. TALAWI, KOTA SAWAHLUNTO - Ridho Gusfajri Ahad; Tri Gamela Saldy (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. PT. Dasrat Sarana Arang Sejati is an underground coal mining company located in Batu Tanjung Village, Talawi District, Sawahlunto City, West Sumatra. PT. Dasrat Sarana Charcoal Sejati has implemented occupational safety and health (K3) in its mining activities, but the implementation is still not optimal. This is due to the lack of signs and K3 posters in every branch of the mining tunnel, the use of personal protective equipment (PPE) is not optimal, some workers do not comply with company regulations resulting in work accidents, the need for revision of job safety analysis (JSA) and operational standards. existing procedures (SOP), as well as making the required JSAs and SOPs. The K3 evaluation that has been implemented uses a questionnaire with a knowledge value of 66.2, an attitude value of 66.3, and an action value of 58.1. Where the overall results of the questionnaire with an average value of 63.5. If the value is adjusted based on the Likert scale, it is in a good range (49-64). Revised and made JSA and SOP on gas checking activities in the work area, jack hammer operation, production activities, buffer maintenance, and coal transportation to the stockpile.